Immunization of children in Africa: strides and challenges (2023)
Background: The African continent is behind by a wide margin in the childhood vaccination race which contributes significantly to the high childhood morbidity and mortality rate from vaccine-preventable diseases in the continent. Some African countries are still struggling to achieve routine immunization coverage for all recommended expanded program on immunization vaccines. Aim: In this study, we aimed to identify the barriers hindering childhood immunization in Africa and to identify the remarkable progress made so far. Materials and Methods: Peer-reviewed articles published in English that focused on the barriers to childhood immunization in Africa and the progress made so far was reviewed. This was achieved by searching relevant search terms in PubMed, Google Scholar, Wiley Online Library, and CINAHL databases dating back from January 2000 to June 2022. Result: A total of 30 papers were reviewed. The barriers include parents’ education status, economic status, and gender/age; place of birth and place of residence; cultural beliefs and religious affiliations; fear of contracting diseases and lack of trust in health public institutions; vaccine awareness and delivery; and dose-specific delays. The achievements include international support and oriented actions, plans for technological integration and its implementation, and domestic immunization-oriented actions and research work. Conclusion: Childhood immunization is still low in Africa with the majority of the countries yet to realize the global immunization targets. Technologies and immunization-related interventions have been implemented to support Africa but more concerted effort and aid are required to reduce vaccine-preventable deaths to the bare minimum.